Adoptive cell transfer: new perspective treatment in veterinary oncology - Bujak, Joanna Katarzyna (Acta Vet Scand, 2018)
Cancer immunotherapy is recently considered the most promising treatment for human patients with advanced tumors and could be effectively combined with conventional therapies such as chemotherapy or radiotherapy. Patients with hematological malignancies and melanoma have benefited greatly from immunotherapies such as, adoptive cell transfer therapy, experiencing durable remissions and prolonged survival. In the face of increasing enthusiasm for immunotherapy, particularly for the administration of tumor-specific T lymphocytes, the question arises whether this method could be employed to improve treatment outcomes for canine patients. It is warranted to determine whether veterinary clinical trials could support comparative oncology research and thus facilitate the development of new cell-based therapies for humans. Herein, we discuss adoptive transfer of T lymphocytes and lymphokine-activated cells for application in veterinary oncology, in the context of human medicine achievements. Furthermore, we discuss potential benefits of using domestic dog as a model for immunotherapy and its advantages for translational medicine. We also focus on an emerging genome-editing technology as a useful tool to improve a T cells’ phenotype.